Effects of ordered hierarchically porous structure on methane reforming performance in solar foam reactor. Issue 37 (April 2020) - Shi, Xuhang; Shuai, Yong; Wang, Fuqiang; Zhang, Chuanxin; Cheng, Ziming; Chen, Xue
Graphical abstract: Highlights: Methane reforming in solar foam reactor with hierarchically porous structure is studied. Hierarchically porous structure can increase the methane conversion. Pore diameter combination with optimum methane conversion at d 1 = 1.0 mm and d 2 = 2.5 mm. Maximum conversion is obtained when the length of the small holes is 0.02 m. Abstract: Hierarchically porous structures are a new type of biomimetic structures that have important applications in several fields. In this study, we aimed to put forward and introduce a new type ordered hierarchical porous structure in the design of solar thermal chemical reaction chambers to utilize CH4 and CO2 . The model of the chambers was established based on the hierarchically porous structure. The effect of hierarchically porous structures on the methane reforming performance of a solar thermal chemical reaction chamber was studied. Based on the finite volume method, FLUENT software was combined with user-defined functions to calculate the effect of different pore size combinations and distributions on the methane conversion. The hierarchically porous structure was found to increase the methane conversion because of the excellent flow characteristics and radiation properties of the structure. The different pore size combinations of the hierarchically porous structure were analyzed, and the optimal pore size combination that results in the maximum methane conversion was obtained. Similarly, the different pore size distributions of the hierarchically porous structure were analyzed, and the optimal pore size distribution was obtained. The conversion of methane is the highest when the length of the small hole section is 0.02 m. This study can provide a new process and reference for the utilization of CH4 and CO2 and design of solar high-temperature thermochemical reaction chambers, based on the hierarchically porous structure. The maximum methane conversion of approximately 85% was found at d 1 = 1.0 mm, d 2 = 2.5 mm, and L 1 = 0.02 m.